Jesus research - an international perspective: the first Princeton-Prague Symposium on Jesus Research, Prague 2005 - Charlesworth, James H. (Princeton-Prague Symposia series on the historical Jesus, 2009)
Preface / Petr Pokorný -- Introduction: Why evaluate twenty-five years of Jesus research? / James H. Charlesworth -- A dead end or a new beginning? : examining the criteria for authenticity in light of Albert Schweitzer / Stanley E. Porter -- Jesus of Galilee : the role of location in understanding Jesus / Jens Schröter -- From old to new : paradigm shifts concerning Judaism, the Gospel of John, Jesus, and the advent of "Christianity" / James H. Charlesworth -- Turning water to wine : re-reading the miracle at the wedding in Cana / Carsten Claussen -- Jesus as an itinerant teacher : reflections from social history on Jesus' roles / Gerd Theissen -- Jesus as a teller of parables : on Jesus' self-interpretation in His parables / Michael Wolter -- "What must I do to inherit eternal life?" : implicit christology in Jesus' sayings about life and the kingdom / Klaus Haacker -- How did Jesus understand His death? : the parables in eschatological prospect / Rudolf Hoppe -- Demoniac and drunkard : John the Baptist and Jesus according to Q 7:33-34 / Petr Pokorný -- "Have you not read ... ?" : jesus' subversive interpretation of scripture / Craig Evans -- A contagious purity: jesus' inverse strategy for eschatological cleanliness / Tom Holmén -- Founding Christianity : comparing Jesus and Japanese "new religions" / Ulrich Luz